Achieving realtime daylight factor computation for modular buildings in generative design. Issue 6 (2nd November 2022) - Marsault, Xavier
Abstract : In generative design, it is imperative for an architect to evaluate very quickly the performance of many buildings produced. Knowing in interactive time the daylighting potential of a generated form at an early stage of its design, with a minimum of parameters, allows to quickly choose among many variants. The daylight factor computational metamodel presented here in the case of modular buildings allows to instantly compare these solutions in order to make judicious choices in dimensioning, without performing time-consuming simulations. Another challenge was to achieve realtime computation for the daylight factor without using a GPU. We have addressed this objective via an hybrid computation both based on physical and statistical modeling, and on a physical-based computation engine specifically used for the optimization of buildings composed of multiple living units. We detail the full implementation in a generative design software leading to impressive computation times of the order of one ms.